UPR-mediated modulation of dendritic cell responses during Toxoplasma gondii infection. (October 2022) - Poncet, Anais; Huot, Ludovic; Bosteels, Victor; Khalife, Jamal; Blanchard, Nicolas; Janssens, Sophie; Marion, Sabrina
Abstract : The modulation of dendritic cell (DC) functions by intracellular parasites remains poorly investigated. Toxoplasma gondii (Tg) infects a wide range of warm-blooded animals including humans. In immune-competent individuals, acute Tg infection is mostly asymptomatic but the parasite chronically persists in the brain and cerebral chronic toxoplasmosis has recently emerged as an underestimated cause of mental disorders and neurodegenerative pathologies. Tg infection induces a robust Th1 immune response that is initiated by type I conventional DC (cDC1). cDC1-mediated T cell activation is critical to restrict parasite growth during acute toxoplasmosis and T cells play a major role in keeping chronic cerebral infection under control. The induction of the Unfolded Protein Response (UPR) in immune cells has recently emerged as a central response, not only to the accumulation of misfolded proteins in the Endoplasmic Reticulum (ER) but also to cellular metabolic variations and infections. In particular, TLR stimulation in macrophages and DC induces the expression of the XBP1s and CHOP transcription factors, which directly activate inflammatory cytokine production. The UPR also modulates MHC class I antigen presentation in cDC1. We found that Tg infection of Bone Marrow Derived DC (BMDC) triggers the IRE1α/XBP1 branch of the UPR and that parasite replication is not required to induce this pathway. Using BMDC deleted for XBP1, we demonstrated that the Tg-induced UPR promotes a unique set of pro-inflammatory cytokines in a MyD88-dependent manner. In addition, our in vitro results suggest that the UPR modulates MHC-I presentation of OVA peptides from OVA-expressing parasites. Finally, using reporter mice, XBP1 activation was confirmed in infected mice and specifically detected in splenic cDC1 during the acute phase of the infection. Mice deleted for IRE1α and XBP1 in CD11c+-DC display a severe susceptibility to infection demonstrating the protective role of DC specific activation of the UPR during Tg infection.